Impact of Education Program upon Nurses' Knowledge towards Children under Mechanical Ventilation at Pediatric Teaching Hospitals in Baghdad City - abbas, Fatima; Mua'ala, Ekbal (Iraqi National Journal of Nursing Specialties, 2013)
Objective: impact of the education program for nurses' knowledge toward children under mechanicalventilation, and to find out the relationships between nurses' knowledge and their general information.Methodology: Quasi experimental study was carried out at the respiratory care units of BaghdadPediatric Teaching Hospitals started from February15th, until September 26th, 2011, A purposive (nonprobability)sample of (23) nurses working in the respiratory care units, were selected from ChildrenWelfare and Pediatric Central Teaching Hospitals. The data were gathered through using of theconstructed multiple choice questionnaire using to evaluate the nurses knowledge using checklist, Thequestionnaire consists of two parts the first one is general information data and the second part isnurses' knowledge multiple choice form used pre test before application of the program and post testafter the application of the program. Descriptive statistical analysis procedure (frequency, and mean ofscore and standard deviation) and inferential analysis procedure (person correlation coefficient and ttestand ANOVA).Results: The findings of the study indicated that nurses have moderate knowledge in pre test. But postevaluation revealed high level of knowledge among nurses at RCU toward children under mechanicalventilation. The program reflects an effect on nurses' knowledge. There were no statistical significantassociation between nurses' knowledge and their general information.Recommendations: The study recommended that great focusing should be directed toward theeducational aspects at respiratory care units by providing educational posters, guidelines, pamphletsand manuals to enhance nurses' knowledge at RCU.